2004
DOI: 10.1002/adma.200306111
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Delivery of Quantum Dots for Live Cell Labeling and Organelle Tracking

Abstract: time. This might be a promising antimicrobial coating for a wide range of materials for biomedical or daily-life applications. ExperimentalPEI (MW 5000 g/mol) was purchased from Hyperpolymers (Freiburg, Germany). All other chemicals, if not stated otherwise, were from Fluka and used without further purification. One gram of PEI was suspended in 50 mL acetone and the mixture was cooled to 0 C . Methacryloyl chloride (0.83 mL dissolved in 35 mL acetone) was added dropwise to the stirred suspension within 20 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
488
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(516 citation statements)
references
References 20 publications
11
488
0
4
Order By: Relevance
“…Although it needs to be demonstrated in future research, it could be expected that similar findings on long-term visibility and symmetric inheritance in daughter cells may be obtained with other methods that enable cytosolic delivery of contrast agents. For instance, electroporation could be explored to this end, although it is typically associated with high cell death 53 and for QD it was reported to result in marked aggregation 54 . Also molecular approaches are developed to this end where contrast agents are conjugated to ligands thathopefully -can translocate the contrast agents into the cytoplasm, either directly across the cell membrane or across endosomal membranes after endocytic uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Although it needs to be demonstrated in future research, it could be expected that similar findings on long-term visibility and symmetric inheritance in daughter cells may be obtained with other methods that enable cytosolic delivery of contrast agents. For instance, electroporation could be explored to this end, although it is typically associated with high cell death 53 and for QD it was reported to result in marked aggregation 54 . Also molecular approaches are developed to this end where contrast agents are conjugated to ligands thathopefully -can translocate the contrast agents into the cytoplasm, either directly across the cell membrane or across endosomal membranes after endocytic uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In a detailed report, Jaiswal et al demonstrated passive endocytotic uptake of hydrophilic QDs capped with dihydrolipoic acid (DHLA) by incubating HeLa cells with solutions containing QDs at concentrations of 400 -600 nM QDs for 3-4 hours (1). QDs entering cells by this pathway remained largely sequestered within endocytic vesicles for several hours (1,11). Other methods for the cellular uptake of QDs that have been reported include: electroporation (14), cationic transfection reagents (11,15) and microinjection (11).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of strategies to deliver QDs to the cells, namely, transfection [65], electroporation, microinjection, uptake into cells via both targeting [66], and passive pathways are common routes for cell labeling and imaging [67]. In many cases, a targeted approach (e.g.…”
Section: Cdte Quantum Dots For Targeted In Vitro and In Vivo Imagingmentioning
confidence: 99%